“We may conclude that:” a corpus-based study of stance-taking in conclusion sections of RAs across cultures and disciplines - Deng, Liming; He, Ping (Frontiers in Psychology, 2023)
Research article conclusions form an important sub-genre in the academic community. This study aims to compare the use of stance markers in English and Chinese research article conclusions and investigate how stance markers may vary in soft and hard sciences. Based on Hyland's stance model, an analysis of stance markers over 20 years was made in two corpora, which were compiled with 180 research article conclusions in each language from four disciplines. It was found that English writers and soft science writers tended to make statements more tentatively by hedges and craft their persona more explicitly through self-mentions. However, Chinese writers and hard science writers made their claims with more certainty by boosters and showed their affective attitude more frequently through attitude markers. The results reveal how writers from different cultural backgrounds construct their stances and also unveil the disciplinary differences involved in stance-taking. It is hoped that this corpus study will inspire future research on stance-taking in the conclusion section and also help cultivate writers' genre awareness.